Semaphorin 7A is protective during inflammatory peritonitis through integrin receptor signaling - Körner, Andreas; Köhler, David; Schneider, Mariella; Roth, Judith M.; Granja, Tiago F.; Eggstein, Claudia; Mirakaj, Valbona; Rosenberger, Peter (Frontiers in Immunology, 2023)
Endothelial Semaphorin 7A (SEMA7A) activates neutrophil migration and enhances inflammation during tissue hypoxia. Yet previous work has also reported anti-inflammatory properties for SEMA7A in the intestinal system during colitis. In an attempt to extend our previous work on SEMA7A we induced peritonitis through the injection of Zymosan A (ZyA) into the peritoneal cavity. Contrary to our findings during hypoxia we found that SEMA7A -/- animals showed increased signs of inflammatory peritonitis, measured through cell count and cytokine release. To further investigate this finding, we subjected intestinal epithelial cells to inflammatory cytokines and found an induction of SEMA7A. In an in vitro model using monocytes and epithelial cells in co-culture, we observed that SEMA7A induced the production of interleukin 10. This production of IL-10 was in dependence dependant uponof the integrin receptors and independent of Plexin C1 (PLXNC1) expression. In a final experiment, we then screened WT animals for the distribution of the SEMA7A target receptors and found that the ITGAV/ITGB1 (CD51/CD29) receptor dominated in the intestinal area. We conclude that SEMA7A has differing functions within this physiological system. The functioning of this process relies on the expression of target receptors for SEMA7A within the affected organ systems.